Effects of Coil Pitch Spacing on Heat Transfer Performance of Nanofluid Turbulent Flow through Helical Microtube Heat Exchanger - H. Rasheed, A.; Alias, H.; D. Salman, S. (International Journal of Engineering and Technology, 2019)
This article provides Numerical simulation on forced convective heat transfer performance of Nanofluid flowing through copper helical microtube of inner diameter of 1.5 mm with different pitch using ANSYS-FLUENT 18.0. The simulation was performed for water, CuO/water, Al2O3/water Nanofluid with 1-2% volume concentration and different pitch of microtube (10, 14 and 18 mm) for turbulent flow regime of Reynolds number varied 5000 to 20000 and governing equations of mass, momentum and heat transfer were solved simultaneously, using the k-e two equations turbulence model. Based on the obtained results, regardless of the concentrations used, the nanofluids exhibited a higher transfer rate than water. This is mainly attributed to the nanoparticles that are in the used nanofluids. The friction factor and the heat transfer rate were enhanced considerably due to the shape and size of the tube, which in this case is a helical microtube. Moreover, the maximum heat transfer performance has been conducted by Al2O3/water Nanofluid with 2% volume concentration and microtube pitch of 18 mm.